A hybrid color texture image classification method based on 2D and semi 3D texture features and extreme learning machine - Tanyildizi, Erkan (Wydawnictwo Sigma-Not Sp Zoo, 2012)
Color texture classification is an important step in image segmentation and recognition. The color information is especially important in textures of natural scenes. In this paper, we propose a novel approach based on the 2D and semi 3D texture feature coding method (TFCM) for color texture classification. While 2D TFCM features are extracted on gray scale converted color texture images, the semi 3D TFCM features are extracted on RGB coded color texture images. The proposed approach is tested on two publicly available datasets. Moreover, comprehensive comparisons are realized with traditional texture analysis tools. The results show the advantages of the proposed method over other color texture analysis methods.
Hybrydowa metoda klasyfikacji obrazów z kolorowa tekstur?
Keywords: Color texture classification; Texture feature coding method; feature extraction